Taming Lattice Strain via Buried Interface Engineering for Reverse-Bias Resilient Perovskite Solar Cells - Du, Niqian; Du, Shanshan; Du, Yaru; Zhang, Xiaobo; Hou, Xiaoyi; Feng, Chi; Xiang, Rongdong; Wu, Xin; Fu, Heping; Liu, Zhiyong; He, Tingwei; Liu, Kaikai (Nano-Micro Letters, 2026)
Inverted perovskite solar cells have achieved exceptional efficiencies, yet their operational stability, particularly under reverse-bias stress, remains a critical challenge. This instability is fundamentally driven by lattice strain, which lowers ion migration barriers and promotes defect formation. Here, we identify the buried hole-transport-layer/perovskite interface as the principal site of strain accumulation. By incorporating 3-fluorothiophene-2-carboxylic acid (3F-2TC) at this buried HTL/perovskite interface, we directly engineer the initial perovskite crystallization template. This buried interface engineering strategy effectively alleviates intrinsic lattice strain, as unambiguously confirmed by grazing-incidence X-ray diffraction analysis. Crucially, we utilize reverse-bias stress as a diagnostic probe to decouple strain relaxation from mere defect passivation, revealing that a low-strain lattice constitutes the primary defense against bias-induced degradation. Consequently, the champion devices achieve a high power conversion efficiency (PCE) of 26.10% and markedly enhanced stability, retaining 91.58% of their initial PCE after 200 h under − 1.0 V reverse bias. This work thereby establishes the buried interface engineering for strain modulation as a generalizable design principle toward efficient and operationally resilient perovskite photovoltaics. Highlights: 1 Modulating perovskite lattice strain, beyond merely managing ion migration or passivating defects, is pivotal for device efficiency and stability. 2 Buried interface engineering simultaneously optimizes the hole-transport-layer, templates film growth and passivates defects, thereby mitigating perovskite lattice strain. 3 Inverted perovskite solar cells achieve a power conversion efficiency of 26.10% with exceptional stability under reverse-bias, thermal, and operational stresses.